Mps1(Mph1) Kinase Phosphorylates Mad3 to Inhibit Cdc20(Slp1)-APC/C and Maintain Spindle Checkpoint Arrests - Zich, Judith (PLoS Genet, 2016)
The spindle checkpoint is a mitotic surveillance system which ensures equal segregation of sister chromatids. It delays anaphase onset by inhibiting the action of the E3 ubiquitin ligase known as the anaphase promoting complex or cyclosome (APC/C). Mad3/BubR1 is a key component of the mitotic checkpoint complex (MCC) which binds and inhibits the APC/C early in mitosis. Mps1(Mph1) kinase is critical for checkpoint signalling and MCC-APC/C inhibition, yet few substrates have been identified. Here we identify Mad3 as a substrate of fission yeast Mps1(Mph1) kinase. We map and mutate phosphorylation sites in Mad3, producing mutants that are targeted to kinetochores and assembled into MCC, yet display reduced APC/C binding and are unable to maintain checkpoint arrests. We show biochemically that Mad3 phospho-mimics are potent APC/C inhibitors in vitro, demonstrating that Mad3p modification can directly influence Cdc20(Slp1)-APC/C activity. This genetic dissection of APC/C inhibition demonstrates that Mps1(Mph1) kinase-dependent modifications of Mad3 and Mad2 act in a concerted manner to maintain spindle checkpoint arrests.